2003
DOI: 10.2118/87324-pa
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Alba Field—Evolution of Completion Practices, Part 2: Openhole Completions, Conventional Gravel Packing After Drilling With SOBM

Abstract: Summary Chevron has been successfully drilling and gravel packing openhole horizontal wells in the Alba field (central North Sea) since 1998, and 13 openhole gravel-packed (OHGP) wells drilled with water-based mud (WBM) are currently in production with no history of sand production. Although these wells have been hugely successful with significant net present value (NPV) returns, it was recognized that the future, mature redrill and infill targets cannot sustain the current costs associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The ideal loading was found to be less than 2% drill solids for injector wells if filter cake clean up was to be effective. Field data from a major partner OHGP project also suggested that drill solids loadings less than 5% had a large impact on productivity indices in producers 9 .…”
Section: Sobm Drill-in Fluidmentioning
confidence: 99%
“…The ideal loading was found to be less than 2% drill solids for injector wells if filter cake clean up was to be effective. Field data from a major partner OHGP project also suggested that drill solids loadings less than 5% had a large impact on productivity indices in producers 9 .…”
Section: Sobm Drill-in Fluidmentioning
confidence: 99%
“…The cell provides adequate empty volume on top of the sandpack to place more than 2 pore volume of gel above the sample top. The cell is connected to a pressure system (1,2,3,4) to apply up to 100 psi overbalance pressure to inject the treatment fluid into the sandpack matrix. A support frame (5) For evaluating the inter-particle bonding effect of the gel, the newly built miniature cone penetrometer shown in Figure 2 was used to measure the penetration resistance of the sandpack before and after treatment to determine the penetration modulus from the most appropriate section of the penetration resistance versus depth curves.…”
Section: Development Of a Miniature Cone Penetrometermentioning
confidence: 99%
“…The elimination of the installation of even a single casing string could save millions of dollars for a single well. Murray et al (2002) described the savings of $3 millions by eliminating a 1000 ft casing run and the change over of drilling mud in the Alba field due to a reduction in operational time, cementing, drilling mud cost and cost associated with mud change over, etc. This highlights the high economic benefit of formation strengthening while drilling.…”
Section: Introductionmentioning
confidence: 99%